Creative writing pedagogies for the twenty-first century - Hunley, Tom C.; Peary, Alexandria, 1970- (Southern Illinois University Press, 2015)
The creative writing workshop: beloved by some, dreaded by others, and ubiquitous in writing programs across the nation. For decades, the workshop has been entrenched as the primary pedagogy of creative writing. While the field of creative writing studies has sometimes myopically focused on this single method, the related discipline of composition studies has made use of numerous pedagogical models. In Creative Writing Pedagogies for the Twenty-First Century, editors Alexandria Peary and Tom C. Hunley gather experts from both creative writing and composition studies to offer innovative alternatives to the traditional creative writing workshop. Drawing primarily from the field of composition studies-a discipline rich with a wide range of established pedagogies-the contributors in this volume build on previous models to present fresh and inventive methods for the teaching of creative writing. Each chapter offers both a theoretical and a historical background for its respective pedagogical ideas, as well as practical applications for use in the classroom. This myriad of methods can be used either as a supplement to the customary workshop model or as stand-alone roadmaps to engage and reinvigorate the creative process for both students and teachers alike. A fresh and inspiring collection of teaching methods, Creative Writing Pedagogies for the Twenty-First Century combines both conventional and cutting-edge techniques to expand the pedagogical possibilities in creative writing studies.